Comparative Review of Endurance Development in Cadets and Students in Track-and-Field Classes and Training at Educational Institutions of State Emergency Service of Ukraine - В. М. Жогло (OVS LLC, 2016)
The purpose of the research is to provide a comparative review of the endurance development in cadets and students in track-and-field classes and training at educational institutions of the State Emergency Service of Ukraine. Research methods: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics of data reduction. Research results. The study resulted in a comparative analysis of the levels of endurance development in the cadets and the first-year students of the School of Psychology and the School of Emergency Rescue Forces of the National University of Civil Defence of Ukraine. Conclusions. The study results prove that the first-year students of the School of Psychology and the School of Emergency Rescue Forces have a low level of endurance (special and aerobic) as compared to the cadets. In this regard, the physical training syllabus ought to include more exercises intended to develop special and aerobic endurance.